2001
DOI: 10.1073/pnas.161099898
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of two genes that together mediate organic solute and steroid transport in the liver of a marine vertebrate

Abstract: Uptake of organic solutes and xenobiotics by mammalian cells is mediated by ATP-independent transporters, and four families of transporters have now been identified. To search for novel organic solute transporters, a liver cDNA library from an evolutionarily primitive marine vertebrate, the little skate Raja erinacea, was screened for taurocholate transport activity by using Xenopus laevis oocytes. In contrast to the organic anion transporters identified to date, a transport activity was identified in this lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
167
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(179 citation statements)
references
References 52 publications
12
167
0
Order By: Relevance
“…Substrates for this transporter include the bile acid taurocholate, other steroids (estrone 3-sulfate and digoxin), and prostaglandin E 2 . 8,9 The present study demonstrates that another steroid, dehydroepiandrosterone sulfate (DHEAS), is also a substrate. The recent work of Dawson and colleagues 7 indicates that Ost␣ and Ost␤ messenger RNA (mRNA) expression along the mouse gastrointestinal tract mirrors that of Asbt, and that both Ost␣ and Ost␤ proteins are localized to the basolateral surface of ileal enterocytes.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Substrates for this transporter include the bile acid taurocholate, other steroids (estrone 3-sulfate and digoxin), and prostaglandin E 2 . 8,9 The present study demonstrates that another steroid, dehydroepiandrosterone sulfate (DHEAS), is also a substrate. The recent work of Dawson and colleagues 7 indicates that Ost␣ and Ost␤ messenger RNA (mRNA) expression along the mouse gastrointestinal tract mirrors that of Asbt, and that both Ost␣ and Ost␤ proteins are localized to the basolateral surface of ileal enterocytes.…”
mentioning
confidence: 68%
“…In the little skate (Leucoraja erinacea), the liver is also a major site of Ost␣ and Ost␤ expression. 8 Although the basis for the species differences in tissue expression is unknown, it is interesting to note that recent studies have identified comparable differences between humans and mice in the expression of a cholesterol transporter, the Niemann-Pick C1-like 1 (NPC1L1) gene. 20 NPC1L1 encodes for a transporter that mediates the intestinal uptake of cholesterol and plant sterols, and appears to be critical in cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the transporter genes that was significantly induced in the colon tissue of Slc10a2 null mice was the mouse ortholog of the organic solute transporter (Ost) ␣ subunit. Wang et al (17) originally identified the Ost transporter complex (Ost␣-Ost␤) from the little skate (Leucoraja erinacea) using expression cloning in Xenopus oocytes (17), and this same laboratory subsequently cloned and expressed the human and mouse orthologs of the skate Ost␣-Ost␤ proteins (14). Remarkably, solute transport requires the expression of two different subunits, a 340-amino acid polytopic membrane protein (Ost␣) and a 128-amino acid single trans-membrane protein (Ost␤), and when co-expressed, these two proteins mediate the transport of bile acids and other sterols (14,17).…”
Section: Analysis Of Transporter Gene Expression In Slc10a2 ϫ/ϫmentioning
confidence: 99%
“…Wang et al (17) originally identified the Ost transporter complex (Ost␣-Ost␤) from the little skate (Leucoraja erinacea) using expression cloning in Xenopus oocytes (17), and this same laboratory subsequently cloned and expressed the human and mouse orthologs of the skate Ost␣-Ost␤ proteins (14). Remarkably, solute transport requires the expression of two different subunits, a 340-amino acid polytopic membrane protein (Ost␣) and a 128-amino acid single trans-membrane protein (Ost␤), and when co-expressed, these two proteins mediate the transport of bile acids and other sterols (14,17). Moreover, human OST␣ and OST␤ are expressed in relative abundance in tissues that also express the ASBT, namely the human small intestine, kidney, and liver (14), suggesting that OST␣-OST␤ may be a basolateral bile acid exporter.…”
Section: Analysis Of Transporter Gene Expression In Slc10a2 ϫ/ϫmentioning
confidence: 99%